Biofabricated 3D in vitro model of fibrosis‐induced abnormal hepatoblast/biliary progenitors' expansion of the developing liver - Matthew Brovold; Dale Keller; Mahesh Devarasetty; Anthony Dominijanni; Rohan Shirwaiker; Shay Soker (Wiley, 2021)
Abstract Congenital disorders of the biliary tract are the primary reason for pediatric liver failure and ultimately for pediatric liver transplant needs. Not all causes of these disorders are well understood, but it is known that liver fibrosis occurs in many of those afflicted. The goal of this study is to develop a simple yet robust model that recapitulates physico‐mechanical and cellular aspects of fibrosis mediated via hepatic stellate cells (HSCs) and their effects on biliary progenitor cells. Liver organoids were fabricated by embedding various HSCs, with distinctive abilities to generate mild to severe fibrotic environments, together with undifferentiated liver progenitor cell line, HepaRG, within a collagen I hydrogel. The fibrotic state of each organoid was characterized by examination of extracellular matrix (ECM) remodeling through quantitative image analysis, rheometry, and qPCR. In tandem, the phenotype of the liver progenitor cell and cluster formation was assessed through histology. Activated HSCs (aHSCs) created a more severe fibrotic state, exemplified by a more highly contracted and rigid ECM, as well higher relative expression of TGF‐β, TIMP‐1, LOXL2, and COL1A2 as compared to immortalized HSCs (LX‐2). Within the more severe fibrotic environment, generated by the aHSCs, higher Notch signaling was associated with an expansion of CK19+ cells as well as the formation of larger, more densely populated cell biliary like‐clusters as compared to mild and non‐fibrotic controls. The expansion of CK19+ cells, coupled with a severely fibrotic environment, are phenomena found within patients suffering from a variety of congenital liver disorders of the biliary tract. Thus, the model presented here can be utilized as a novel in vitro testing platform to test drugs and identify new targets that could benefit pediatric patients that suffer from the biliary dysgenesis associated with a multitude of congenital liver diseases.